Synthesis and EPR studies of porphyrazines with bulky substituents - Keskin, Bahadir; Koseoglu, Yueksel; Avciata, Ulvi; Gul, Ahmet (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Magnesium porphyrazinate substituted with eight 4-tert-butylphenylthio-groups on the peripheral positions has been synthesized by cyclotetramerization of 1,2-bis(4-tert-butylphenylthio)maleonitrile in the presence of magnesium butanolate. The metal-free derivative was obtained by its treatment with trifluoroacetic acid and further reaction of this product with copper(II) acetate, zinc(II) acetate and cobalt(II) acetate led to the metal porphyrazinates (M = Cu, Zn, Co). These new compounds have been characterized by elemental analysis, together with FT-IR, H-1 NMR, UV-Vis spectral data. By using EPR technique, room temperature paramagnetic properties of Cu(II) doped porphyrazine sample as powder and solution forms were measured. The first-derivative EPR signals taken from as powder and solution forms shows that the sample is axially symmetric. The trend g(parallel to) > g(perpendicular to) > 2 indicates that the unpaired electron is located mainly in the d(x2-y2) orbital (B-2(1) as ground state). (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: porphyrazine; EPR; copper; zinc; cobalt; PHTHALOCYANINES; PORPHYRINS; COMPLEXES; Chemistry; Crystallography